B Cells: The Old New Players in Reproductive Immunology - Fettke, Franziska; Schumacher, Anne; Costa, Serban-Dan; Zenclussen, Ana Claudia (Frontiers in Immunology, 2014)
Reproductive immunology research has long focused on T cell responses to paternal antigens and tolerance mechanisms supporting fetal well-being. The participation of B cells herein was not widely studied. Because of the fascinating immunological uniqueness of pregnancy, it is however to be expected that such pleiotropic cells play a considerable role. In fact, on the one hand B cells contribute toward pregnancy tolerance by secreting the immunomodulatory cytokine IL-10 but on the other hand can seriously harm pregnancy because of their capacity of producing autoantibodies. As for protective B cells, new evidences in mouse models arise suggesting that IL-10 producing B cells, the so-called B10 cells, help in maintaining tolerance toward semi-allogenic fetal antigens. They may be also important to fight danger signals at the fetal-maternal interface as, e.g., in the case of infections with the aim to restore the disrupted fetal tolerance. In human pregnancies, IL-10 producing B cells increase with pregnancy onset but not in the case of spontaneous abortions. In vitro, they are able to suppress TNF-α production by T cells from pregnant individuals. Their generation and functionality will be discussed throughout this review article. B cells can be deleterious to pregnancy as well. Aberrant B cell compartment is associated with obstetric pathologies. In particular, the capacity of B2 cells to produce specific autoantibodies or of B-1a B cells to secrete natural autoantibodies that can turn autoreactive will be discussed herein.